PERENCANAAN PENGEMBANGAN HUTAN RAKYAT DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - mahvudh, Andi; Hamzari, .; Arianingsih, ida (Universitas Tadulako, 2018)
Community forests are those that grow on community land and are managed by the community itself. This research was conducted in Labuan Toposo Village Labuan Sub-district Donggala Regency on May to August 2016. This research intends to identify the development planning of community forest in Labuan Toposo village. Data in this research is primary and secondary and were collected through interview guides or questionnaires containing statements about community forests and the constraints on community forest development planning. Data were analyzed through perspective method using qualitative approach or descriptive qualitative research method in scale of 1-3-5 (Scale Modification of Likert). This research revealed that some of people in the community have not understand the importance of forest development, they only use the land for agricultural without any awareness of the importance of forests for the survival of their surroundings.Keywords: Planning, Development, Forest of Community.